Efficacy and safety of sirolimus in the treatment of vascular malformations: A protocol for systematic review and meta-analysis. Issue 40 (2nd October 2020) - Dong, Jianyong; Han, Deting; Wang, Desheng; Lu, Huijun; Wang, Xiaoliang
Abstract: Background: The pathophysiologic of vascular malformations is still unclear, and the treatment of vascular malformations is a challenge. With improvement in the understanding of pathogenesis of vascular malformations, sirolimus has been a promising and effective treatment. As so far, there is absent convincing evidence to confirm the efficacy of sirolimus for vascular malformations. The purpose of this study was to evaluate the effectiveness and safety of sirolimus in the treatment of vascular malformations. Methods: The literatures about the management of vascular malformations with sirolimus would be searched from databases of MEDLINE, EMBASE, PubMed, Web of Science, Clinicaltrials.org., Cochrane Library, China Biology Medicine Database (CBM), Wan Fang Database, China National Knowledge Infrastructure Database (CNKI), and VIP Science Technology Periodical Database. We will search each database from inception or 1995 to August 20, 2020. Two researchers worked independently on literature selection, data extraction and quality assessment. The efficacy and safety of sirolimus in the treatment of vascular malformations were the main outcomes. Adverse events after sirolimus were evaluated as the secondary outcomes. The included studies will be analyzed by Review Manager 5.3. If the results are applicable, meta-analysis would also be performed. Results: The study will evaluate the efficacy and safety of sirolimus in the treatment of vascular malformations based on current evidence. Conclusion: The conclusion of this study will provide more reliable, evidence-based data for the use of sirolimus in the treatment of vascular malformations. PROSPERO registration number: CRD42020167881.